Evaluation of photosensitizer-containing superhydrophobic surfaces for the antibacterial treatment of periodontal biofilms - Tonon, Caroline Coradi (2022)
Antimicrobial photodynamic therapy (aPDT) is a promising approach to control biofilms involved in periodontal diseases. However, certain challenges, such as staining of teeth, preferential interaction of photosensitizer (PS) with Gram-positive versus Gram-negative bacteria, and insufficient oxygen in hypoxic periodontal pockets have presented barriers to its use in the clinic. To overcome these challenges, a novel superhydrophobic (SH) film that generates airborne singlet oxygen has been developed. The SH-aPDT approach isolates the PS onto a topologically rough solid SH film on which channels allow air to diffuse to the PS surface, thus ensuring sufficient oxygen supply. Upon illumination, gas phase singlet oxygen (1O2) is produced and diffuses from the SH surface to the underlying biofilm. The killing efficacy was assessed as a function of transmitted fluence (17.9–89.5 J/cm2) and chorin e6 loading (96–1110 nmol/cm2) by counting of colony forming units, biofilm metabolism by XTT and confocal microscopy. The decrease in viability of both Gram-positive and Gram-negative bacteria in a multi-species biofilm was found to be linearly dependent on the fluence as well as the loading of the PS up to 71.6 J/cm2 when 1110 nmols/cm2 of chlorin e6 was used. A > 4.6 log bacterial reduction was observed under these conditions (p < 0.05). This novel SH-aPDT approach shows promise as an effective method to disinfect multi-species bacterial biofilms associated with periodontal disease and will be evaluated in animal models in future studies.